2015
DOI: 10.3390/polym7111515
|View full text |Cite
|
Sign up to set email alerts
|

Leads from Physical, Chemical, and Thermal Characterization on Cytotoxic Effects of Xylan-Based Microparticles

Abstract: Interfacial cross-linking (ICL) has been considered a feasible technique to produce polysaccharide-based microparticles (PbMs), even though only a few studies have been concerned with their biocompatibility. In this work, PbMs were prepared by the ICL method and characterized in regard to their in vitro biocompatibility, chemical linkages, and physical and thermal properties. First, the cell viability assay revealed that PbMs toxicity was concentration-dependent. Then, it was observed that the toxicity may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 33 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…Therefore, the presence of some broken AXM could be related to the freeze-drying process used prior to the SEM analyses. The freeze-drying process involves the formation of ice-crystals which can disrupt the structure of the material as has been reported previously in freeze-dried xylan-based microparticles [59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the presence of some broken AXM could be related to the freeze-drying process used prior to the SEM analyses. The freeze-drying process involves the formation of ice-crystals which can disrupt the structure of the material as has been reported previously in freeze-dried xylan-based microparticles [59].…”
Section: Discussionmentioning
confidence: 99%
“…In that study, the cell viability values (~96%) were close to those observed in the non-cancerous cell line (CCD 841 CoN) treated with AXM, which was evaluated in the present study. Moreover, Rodrigues et al [59] found that xylan was biocompatible with HeLa cells in the range of 4.1–12.4 mg/mL due to the non-toxic and highly safe characteristics of the biopolymer. The observations found in the present study demonstrate that AX and AXM exhibit good biocompatibility and do not have a cytotoxic effect on the normal human colon cell line CCD 841 CoN.…”
Section: Discussionmentioning
confidence: 99%
“…The preparation of microparticles based on hydrophilic polymers, such as polysaccharides derivatives, using techniques based on emulsion templates, majorly requires the use of organic solvents in order to form the hydrophilic and hydrophobic phases in which the internal hydrophilic phase contains the polymer [1][2][3]. In addition, together with the use of crosslinkers such as glutaraldehyde and terephthaloyl chloride, the microparticles produced by this way may present an important degree of toxicity [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…As previously mentioned, the preparation of polysaccharide-based microparticles, including xylan-based microparticles (XBM), mostly requires the use of organic/harmful solvents such as cyclohexane, and crosslinkers, such as terephthaloyl chloride, during their preparation [1,9,10]. On this behalf, the water-in-water emulsion approach can produce microparticles by the mixture of two immiscible aqueous polymeric solutions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation